Egypt’s Water Problems and Solutions: The Hydro-Politics of The Nile River - Moses, Ige Kehinde (Covenant University Journal of Politics and International Affairs, 2021)
The Nile River dictated Egypt’s fate for thousands of years. It lets life grow at its banks. The journey down the River Nile starts in Assuan-Assouan from the Nile Island of Elephantine to the Camel market in Daraw and unto Louxor with its famous temples and the Valley of the Kings which has been a major source of tourism and exploration for the nation of Egypt [Weeks, Hetherington, Bakhoum; 2014]. Near Amarna in Middle Egypt, the locals proudly preserve their traditions. The river then turns into a delta after Kairo (Le Caire) and enters the Mediterranean Sea after 6,853 kilometers. While some may perceive Egypt’s attempt to monopolize the Nile as Cairo’s quest for Hegemony, to others, it is merely a struggle for survival. As the Nile is Egypt’s primary source of water. Furthermore, the dilemma of an increasing population and the continuous decline of the water supply has altogether made the survival of the region questionable. The middle east has experienced numerous environmental concerns and these concerns are so sensitive that they threaten the very survival of the region. Hence, beyond the Egyptian State, water resources have become increasingly scarce and the prospects of possible importation of water as a natural resource have become even more likely than ever. The majority of the countries in the middle east lack access to sanitary water; and in addition to its both strategic and controversial location, it is safe to say however wealthy the middle east is today, many of its member states face some degree of a water crisis. Nations such as Yemen, the United Arab Emirates, Saudi Arabia and Iraq find themselves in more compound conditions as they face distinctive difficulty that require worldwide, instantaneous consideration. For this research, I will look to interrogate the dynamics of international relations between Egypt, Ethiopia, and Sudan with an appraisal as to the implications and repercussions of Ethiopia’s Grand Renaissance Dam.